Suboptimal Light Conditions Influence Source-Sink Metabolism during Flowering - Christiaens, Annelies; De Keyser, Ellen; Pauwels, Els; De Riek, Jan; Gobin, Bruno; Van Labeke, Marie-Christine (Frontiers in Plant Science, 2016)
Reliance on carbohydrates during flower forcing was investigated in one early and one late flowering cultivar of azalea (Rhododendron simsii hybrids). Carbohydrate accumulation, invertase activity, and expression of a purported sucrose synthase gene (RsSUS) was monitored during flower forcing under suboptimal (natural) and optimal (supplemental light) light conditions, after a cold treatment (7°C + dark) to break flower bud dormancy. Post-production sucrose metabolism and flowering quality was also assessed. Glucose and fructose concentrations and invertase activity increased in petals during flowering, while sucrose decreased. In suboptimal light conditions RsSUS expression in leaves increased as compared to optimal light conditions, indicating that plants in suboptimal light conditions have a strong demand for carbohydrates. However, carbohydrates in leaves were markedly lower in suboptimal light conditions compared to optimal light conditions. This resulted in poor flowering of plants in suboptimal light conditions. Post-production flowering relied on the stored leaf carbon, which could be accumulated under optimal light conditions in the greenhouse. These results show that flower opening in azalea relies on carbohydrates imported from leaves and is source-limiting under suboptimal light conditions.